FAKTOR-FAKTOR YANG MEMPENGARUHI PERSEPSI WAJIB PAJAK MENGENAI ETIKA ATAS PENGGELAPAN PAJAK (TAX EVASION) - Ade Mentari; Halimatusyadiah (UNIB Press, 2024)
The purpose of this study is to examine the effect of tax fairness, tax system, tax discrimination, technology and information of taxation on taxpayer perception about the ethics of tax evasion. The data used in this study were primary data. The primary data were obtained from questionnaires distributed to individual taxpayers in Bengkulu City. The number of questionnaires that distributed were 110, but only 108 questionnaires that could be proceed.The data were analyzed by using multiple linear regression analysis with SPSS program. The results of the study showed that the tax fairness had negative effect on taxpayer perception about the ethics of tax evasion, while tax discrimination had positive effect on taxpayer perception about the ethics of tax evasion. In contrast, tax system, technology and information of taxation did not effect on taxpayer perception about the ethics of tax evasion.